A cross-sectional study of dietary and urinary soy isoflavones about coal-burning fluorosis in Guizhou, China - Han, Hua; Li, Yameng; Li, Peimin; Liu, Lu; Zheng, Xingting; Zhang, Yuanmei; Liu, Min; Zhang, Xiaogang; Tang, Ling; Gao, Manman; Tao, Na; Liu, Jun (Frontiers in Nutrition, 2025)
ObjectivePrevious research showed soy isoflavones have antioxidant properties beneficial to bone health, but no epidemiological studies reported effects of soy isoflavones on fluorosis. Therefore, the aim of this study was to investigate the relationship between soy isoflavones in diet/urine and coal-burning fluorosis.MethodsA comprehensive cross-sectional study with 896 participants in Zhijin County, Guizhou, China, assessed dietary intake through face-to-face interviews using a 75-item food frequency questionnaire. Urine samples were analyzed for soy isoflavone concentrations by HPLC. Unconditional logistic regression models were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for associations.ResultsWe observed a significant inverse association between dietary soy isoflavones and fluorosis. The adjusted OR (95% CI) in the highest quartile of intake compared with the lowest was 0.61 (0.38–0.97) (p-trend = 0.032) for total soy isoflavones intake, 0.59 (0.37–0.95) (p-trend = 0.032) for daidzein intake. Results of soy isoflavones in urine were consistent with the dietary results.ConclusionSoy isoflavones are associated with the occurrence of coal-burning fluorosis.